Micronutrient Deficiency and Burden of Anaemia: A Population-based Study from Haryana, India - Suniti Yadav; Mamta Kumari Thakur; Naorem Devi Kiranmala; Kallur Nava Saraswathy (National Journal of Laboratory Medicine, 2018)
Introduction: Anemia is a state where there is reduction in the number of red blood cells or haemoglobin levels (a major component in red blood cells), resulting in the lowering of overall oxygen-carrying capacity of the blood. In addition to this, nutritional anemia is caused due to deficiency of micronutrients such as folate and vitamin B12 that are vital for the development of red blood cells. Aim: To assess the role of micronutrient (i.e. folate and vitamin B12) deficiency in the causation of anaemia. Material and Methods: Cross-sectional study on apparently healthy individuals of either sex aging 30-65 years from nine villages of Palwal district of Haryana, Northern India was conducted 2012 month of September to November, 2013 February to April, July to November 2014. Complete Blood Count (CBC) was done using Sysmex-KX 21 (Transasia) and homocysteine, vitamin B12 and folate levels were measured by chemilumniscence using Immulite-1000 (SiemensDiagnostic-Products, and Flanders, NJ, USA). Anaemia status was categorised into macrocytic, normocytic and microcytic anemia, based on Haemoglobin (Hb) and Mean Corpuscular Volume (MCV) levels. Results: Prevalence of anaemia, folate deficiency and vitamin B12 deficiency was found to be 51.9%, 36.9% and 45.5% respectively. Anaemia was found to be highest in the age group 41-50 years. Individuals with macrocytic, microcytic and normocytic anaemia showed high prevalence of micronutrient deficiency i.e. vitamin B12 and folate. Conclusions: Majority of anaemic in an apparently healthy population indicates a forthcoming economic burden in the community. Micronutrient deficiencies along with hyperhomocysteinemia among anaemics indicate a plausible co-existence of iron and vitamin B12 deficiency in this cohort. The study hints towards the need for awareness regarding dietary sources of micronutrients along with their supplementation among vegetarian populations.